Institutional interplay in global environmental governance: lessons learned and future research - Joshua Philipp Elsässer; Thomas Hickmann; Sikina Jinnah; Sebastian Oberthür; Thijs Van de Graaf (International Environmental Agreements: Politics, Law and Economics, 2022)
Over the past decades, the growing proliferation of international institutions governing the global environment has impelled institutional interplay as a result of functional and normative overlap across multiple regimes. This article synthesizes primary contributions made in research on institutional interplay over the past twenty years, with particular focus on publications with International Environmental Agreements: Politics, Law and Economics. Broadening our understanding about the different types, dimensions, pathways, and effects of institutional interplay, scholars have produced key insights into the ways and means by which international institutions cooperate, manage discord, engage in problem solving, and capture synergies across levels and scales. As global environmental governance has become increasingly fragmented and complex, we recognize that recent studies have highlighted the growing interactions between transnationally operating institutions in the wake of polycentric governance and hybrid institutional complexes. However, our findings reveal that there is insufficient empirical and conceptual research to fully understand the relationship, causes, and consequences of interplay between intergovernmental and transnational institutions. Reflecting on the challenges of addressing regulatory gaps and mitigating the crisis of multilateralism, we expound the present research frontier for further advancing research on institutional interplay and provide recommendations to support policy-making.
Keywords: 330; Institutional interplay; Transnational institutional interplay; Global environmental governance; Transnational governance; Multilateral environmental agreements